A Few Remarks about the Lectionary after Fifty Years of Existence - Sławiński, Henryk (Verbum Vitae, 2022)
The aim of the paper is to present briefly first of all the history of the development of the Lectionary for the use in the Holy Mass, then to summarize the principal of the present lectionary and it’s ecumenical meaning, and more specifically it’s influence on the protestant lectionary. Based on these historical facts and the recent documents of the Holy See, the proposal of the partial renewal of the Sunday Lectionary will be discussed. The main method used in the study is the analysis of the historical sources, documents of the Holy See and theological studies. The critical analysis, and then comparative method will lead to synthetical presentation of postulates of the partial renewal of the present lectionary after fifty years of usage in the liturgy. The conclusion of the analysis provides the suggestions for the enrichment of the lectionary first of all, with the passages from the Old Testament read in their whole context, not only according to the harmonization with the text of the Gospel; secondly, with the thematic selection of the second reading compatible with the first reading, and the Gospel reading; thirdly, with the texts pointing out the role of women in the history of salvation.